Causal relationship between inflammatory cytokines and autoimmune thyroid disease: a bidirectional two-sample Mendelian randomization analysis - Yao, Zhiwei; Guo, Fengli; Tan, Yanlu; Zhang, Yiyuan; Geng, Yichen; Yang, Guang; Wang, Song (Frontiers in Immunology, 2024)
Background:Autoimmune thyroid disease (AITD) ranks among the most prevalent thyroid diseases, with inflammatory cytokines playing a decisive role in its pathophysiological process. However, the causal relationship between the inflammatory cytokines and AITD remains elusive.A two-sample Mendelian randomization (MR) analysis was performed to elucidate the causal connection between AITD and 41 inflammatory cytokines. Genetic variations associated with inflammatory cytokines were sourced from the FinnGen biobank, whilst a comprehensive meta-analysis of genome-wide association studies (GWAS) yielded data on Graves disease (GD) and Hashimoto thyroiditis (HT). Regarding the MR Analysis, the Inverse variance-weighted (IVW), MR-Egger, and Weighted median (WME) methods were utilized. Additionally, sensitivity analysis was conducted using MR-Egger regression, MR-pleiotropy residual sum, and outliers(MR-PRESSO).Results: 7 causal associations were identified between inflammatory cytokines and AITD. High levels of TNF-β and low levels of SCGF-β were indicative of a higher risk of GD. In contrast, high levels of IL-12p70, IL-13, and IFN-γ and low levels of MCP1 and TNF-α suggested a higher risk of HD. Moreover, 14 causal associations were detected between AITD and inflammatory cytokines. GD increases the levels of MIP1β, MCP1, MIG, IP10, SDF1α, PDGFbb, βNGF, IL2ra, IL-4, and IL-17 in blood, whilst HD increases the levels of MIG, IL2ra, IP10, IL-16 levels.Our bidirectional MR analysis revealed a causal relationship between inflammatory cytokines and AITD. These findings offer valuable insights into the pathophysiological mechanisms underlying AITD.